2015
DOI: 10.4236/ojped.2015.51011
|View full text |Cite
|
Sign up to set email alerts
|

Management of Specific Complications after Congenital Heart Surgery (I)

Abstract: In addition to the general consequences of surgery and cardiopulmonary bypass , lesion-specific complications can occur after surgery for congenital heart disease. It is important for the pediatric intensive care specialist to fully understand the preoperative anatomy and the intraoperative details of these patients. This allows a timely and appropriate treatment of general and lesion-specific complications. In this article we provide a list of commonly-performed surgical procedures and possible associated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A review of the literature suggests that paediatric patients with CHD pay a high price because of the need for long‐term regular follow‐ups and the consumption of medication. Some paediatric patients may even encounter post invasive procedures complications, such as pulmonary hypertension, arrhythmias and residual stenosis (Andrés, Miño, Diéguez, Boni, & Moreno, ). A longitudinal study revealed that CHD brought impairments to more than half of school‐age children in relation to multiple developmental domains including cognitive, neurological status, motor, academic, language and speech, and severely affected their quality of life (Bellinger & Newburger, ).…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature suggests that paediatric patients with CHD pay a high price because of the need for long‐term regular follow‐ups and the consumption of medication. Some paediatric patients may even encounter post invasive procedures complications, such as pulmonary hypertension, arrhythmias and residual stenosis (Andrés, Miño, Diéguez, Boni, & Moreno, ). A longitudinal study revealed that CHD brought impairments to more than half of school‐age children in relation to multiple developmental domains including cognitive, neurological status, motor, academic, language and speech, and severely affected their quality of life (Bellinger & Newburger, ).…”
Section: Introductionmentioning
confidence: 99%